Кулінарні особливості української кухні - Мякшин, А. С. (ХНУРЕ, 2020)
These theses are devoted to describing the features of Ukrainian cuisine. It tells about the selection of ingredients, methods of preparation and formation of dishes. It also touches on the historical aspects that influenced the formation of Ukrainian cuisine as national and unique.
Keywords: культурне розмаїття; українознавство; традиції; культура